IMPACT OF CHEMICAL THINNING TO IMPROVE FRUIT CHARACTERISTICS OF DATE PALM CULTIVAR KHALAS - & et al., Ghazzawy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field study was conducted to observe the effects of chemical fruit thinning and their time of application on fruit yield and quality of date palm cv. Khalas at Date Palm Research Center of Excellence, King Faisal University, Saudi Arabia. Fourteen date palm trees were randomly selected for the experiment, which was laid out on two-factorial randomized complete block design having six replicates for each treatment. Factor-one comprised of the six chemical (ammonium thiosulphate at 1, 2, and 3% and ethephon at 100, 200 and 300ppm) excluding control, whereas the second factor was the time of application of these two chemical thinners (5 and 10 days after pollination). The findings of this study indicated that the chemical fruit thinning had definite effects on virtually all fruit quality characteristics. Early application of chemical thinners after 5 days of pollination, significantly decreased the total fruits drop percentage and enhanced number of retained fruits, bunch weight, yield per palm, fruit color, fruit weight and length, seed weight, TSS, total and reducing sugars. On the other hand, among chemical thinners, the application of ethephon at 300 ppm significantly improved previously mentioned parameters. Similarly, ethephon at 200 or ATS at 3% also showed promising results. It is therefore, concluded that the application of ethephon at 200 or 300ppm after 5 days of pollination influenced significantly regarding fruit yield and quality parameters of date palm cv. Khalas.